2020
DOI: 10.1088/1757-899x/755/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Refueling Mission-3—an overview

Abstract: Robotic Refueling Mission-3 (RRM3) is an external payload on the International Space Station (ISS) to demonstrate the techniques for storing and transferring a cryogenic fuel on orbit. RRM3 was designed and built at the National Aeronautics and Space Administration/Goddard Space Flight Center (NASA/GSFC). Initial testing was performed at GSFC using liquid nitrogen and liquid argon. Final testing and flight fill of methane was performed at the NASA Kennedy Space Center (KSC) to take advantage of KSC’s facilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“… Kassemi et al 47 Comparison of CFD and experimental data from 3 different datasets of self-pressurization HP Ground, ISS, Space Shuttle Hydrogen, PnP, Freon-113 Only experimental controlled and known boundary conditions allow a good agreement with experiments and CFD of two-phase systems. Breon et al 48 Storage and transfer of a cryogenic fuel on orbit ZBO TO HP/AP TVS Ground, ISS Nitrogen, Argon, Methane 4 months Zero Boil-Off methane storage by a cryocooler. Problem during on-orbit venting expelled all methane prior to transfer demonstration.…”
Section: Application Perspectives and Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“… Kassemi et al 47 Comparison of CFD and experimental data from 3 different datasets of self-pressurization HP Ground, ISS, Space Shuttle Hydrogen, PnP, Freon-113 Only experimental controlled and known boundary conditions allow a good agreement with experiments and CFD of two-phase systems. Breon et al 48 Storage and transfer of a cryogenic fuel on orbit ZBO TO HP/AP TVS Ground, ISS Nitrogen, Argon, Methane 4 months Zero Boil-Off methane storage by a cryocooler. Problem during on-orbit venting expelled all methane prior to transfer demonstration.…”
Section: Application Perspectives and Backgroundmentioning
confidence: 99%
“…A quite unique technological demonstrator for the storage and transfer of liquid methane was developed by ref. 48 : the Robotic Refueling Mission 3 (RRM3). This mission extends RRM1 and RRM2, which demonstrated satellite refueling operations in a platform installed outside the ISS.…”
Section: Application Perspectives and Backgroundmentioning
confidence: 99%
“…[45] (a) piezo bimorph bender; a kind of piezo-electric material used as both sensors and as actuators; [46,47] (b) utilization of piezo-electric sensor and actuators utilized on the free-floating flexible space robot simulator in figure 8b [48] simulating hardware such as the Robotic Refueling Mission-3. [49] Subfigure b is taken from [47] a publication that is a work of the U.S. Government as defined in Title 17, United States Code, Section 101. Copyright protection is not available for this work in the United States.…”
Section: Frequency Responses Of Step and Periodic Functions [24]mentioning
confidence: 99%
“…During the Robotic Refueling Mission #3 (RRM3), evidence from both temperature sensors and Radio Frequency Mass Gauging results suggested that when the cryocooler was turned off, the ullage moved to the cryocooler connection point. [4,5] The RRM3 tank contained a sponge propellant management device, controlling approximately 80% of the tank. When the cryocooler was on, the ullage bubble appeared to be contained above the sponge in the area generally allocated for it.…”
Section: Introductionmentioning
confidence: 99%